Default in Ijarah Contracts For MUA Services: A Sharia Economic Law Perspective - Mubarokah, Nazilatul; Cahyono, Eko Arief; Anang, Arif Al (Al-Risalah, 2026)
This study analyzes the practice of default in the ijarah contract for Make Up Artist (MUA) services in Maibit Village and assesses its compliance with Islamic economic law principles. Employing an empirical legal approach (socio-legal research) with qualitative methods including in-depth interviews, field observations, and literature review of muamalah jurisprudence this study examines the forms, causes, and implications of contractual violations in village-based creative services. The findings reveal that MUA service contracts in Maibit Village are predominantly oral, lacking adequate written documentation, which leads to defaults in the form of delayed or reduced wage payments and uncompensated additional services. These practices violate the principles of justice ('adl), trust (amanah), and contractual fulfillment (wafā' bil 'uqūd) in Islamic economic law. The novelty of this study lies in its empirical analysis of ijarah defaults in micro creative services at the village level, positioning service providers—rather than consumers as the primary subject of legal protection under sharia economic law. This study contributes to the literature by extending ijarah contract analysis from the formal sector to the informal creative economy and recommends the adoption of detailed service agreements, simple written documentation, and advance payment ('urbun) mechanisms to strengthen contractual commitment and safeguard service providers' economic rights.